A "prehistory" to Chinese debates on the survival of death by the spirit, with a focus on the term shishen 識神/shenshi 神識 - Radich, Michael (Journal of Chinese religions, 2016)
In fifth- and sixth-century China, one set of debates between Buddhists and their opponents famously focused on the Buddhist claim that "the spirit survives [death]" 神不滅. Prior scholarship has tended to focus on the development of relevant concepts only beginning in the early fifth century. However, building on work by Kawano, Itō, Nattier, Zacchetti, and Park, this paper argues that important predecessors to the concepts deployed by Buddhist participants in those debates can already be found in the translation literature of the third and fourth centuries. The present paper is part of a larger study of antecedents to the doctrine of *amalavijñāna ("taintless consciousness") in the works of Paramārtha 真諦 (499-569), and therefore focuses in particular on terms relating to "consciousness" to label the transmigrating entity. In concert with prior and parallel studies, this study forms part of a larger argument that *amalavijñāna had important background in both India and China.